A cross‐national analysis of affirmative action: an evolutionary psychological perspective - Yang, Chulguen; D'Souza, Geeta C.; Bapat, Ashwini S.; Colarelli, Stephen M. (Managerial and Decision Economics, 2006)
Abstract Affirmative action (AA) is a government policy permitting employers and universities to give preferential treatment to applicants from specific (e.g. racial) groups. We present a comparative analysis of AA in six countries (India, USA, Malaysia, Canada, South Africa, and Brazil) and explain similarities among these programs according to universal psychological mechanisms and variation according to cultural–historical contexts. It appears that similarities in contextual conditions (e.g. democratic government, multi‐ethnic states) interact with ancient psychological mechanisms (e.g. fairness, cheater detection, alliance tracking) to provide at least part of the motivation for the development and expansion of AA, despite its problematic consequences. Copyright © 2006 John Wiley & Sons, Ltd.
Keywords: dept.mgt; peer-reviewed

Role modeling as a pedagogical strategy in entrepreneurship education for women and girls: An interactive model of transformational learning - Oppedisano, Jeannette; Laird, Kenneth R (New England Journal of Entrepreneurship, 2006)
This article presents a pedagogical model that utilizes students as primary researchers in the identification, interviewing, and then reporting on women entrepreneurs as a major component of a multidisciplinary entrepreneurship course. The purpose of the course is to attract students who may not be familiar with the entrepreneurship concept itself, the role of women in such economic ventures, or the possibilities for people like themselves in such a career avenue. Students are exposed to the accomplishments of women entrepreneurs throughout U.S. history in the broad categories of agriculture and mining; construction; communication; manufacturing; service (both for profit and not-for-profit); transportation; and wholesale and retail trade. This content experience is then enhanced by the studentsʼ own direct interaction with and interviewing of women entrepreneurs. The implementation, potential outcomes, and possible adaptations of the course are described, and this transformational learning process model is illustrated. © Published by DigitalCommons©SHU, 2006.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/112-478-351-659-477 tex.type: [object Object]
Keywords: dept.mgt